ANALISIS PENEGAKAN HUKUM PERLINDUNGAN KONSUMEN DALAM KARTEL PENJUALAN SEPEDA MOTOR SKUTER MATIK HONDA-YAMAHA (Studi Kasus Putusan Kasasi MA RI No. 217K/Pdt.Sus-KPPU/2019) - Munathsir Mustaman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
Normative juridical research methodologies with a statutory approach are used to examine customer protection in the 110-125 CC of Honda-Yamaha automatic scooter motorbike sales cartel and legal measures to recover consumer losses. Since the KPPU decision 04/KPPU-I/2016 simply addresses the legal certainty of the cartel elements under Article 5 paragraph (1) Law 5/1999, it can be concluded that consumer protection law enforcement has not been taken into account in the cartel selling automatic scooters 110-125 CC of Honda-Yamaha. Civil actions for reimbursement for unlawful activities, complaints to the Dispute Resolution Agency (BPSK), and complaints to the National Consumer Protection Agency (BPKN) that can be used to recover consumer losses in the Honda-Yamaha automatic scooters 110–125 CC cartel. As a consequence, a legal mechanism is required to allow consumers to recover losses incurred due to anti-competitive agreements and/or conduct by business actors. Anti-Monopoly Law and/or Customer Protection Law laws should be implemented by the government to determine how to recover consumer losses caused by the Honda-Yamaha automatic scooters 110 – 125 CC cartel, as well as other consumer losses caused by anti-competitive law violations.